Examining the Relationship Between Leadership Style, Work Motivation, and Work Productivity - Lbn. Raja, Edward Alezandro; Rozaini; Lbn. Raja, Togu Harlen; Lbn. Raja, John G (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study examines the influence of leadership style and work motivation on work productivity at the Indonesian Business and Computer Institute. The research is driven by the strategic role of human resource management in enhancing organizational performance, where leadership and motivation are often considered key drivers of employee productivity. The purpose of this study is to determine whether these two factors significantly contribute to improving productivity within the institution. Using a quantitative approach, data were collected through questionnaires distributed to all 48 employees and lecturers, employing a saturated sampling technique to ensure complete representation. The data were analyzed with multiple linear regression, supported by validity, reliability, and classical assumption tests. The results indicate that both leadership style and work motivation have a statistically significant and positive effect on productivity. The regression analysis confirmed model validity, with leadership style contributing a coefficient of 0.300 (t = 4.286, p < 0.001) and work motivation showing a stronger coefficient of 0.350 (t = 5.645, p < 0.001). These findings emphasize the importance of effective leadership practices and robust motivational strategies in enhancing employee productivity.